Evaluasi Kualitas Beton Struktur Pier Head Jalan Tol Km149 Padaleunyi, Bandung Menggunakan Metode Ultrasonic Pulse Velocity - Azzam, Abdullah; Lenggogeni; Yasinta, Rezi Berliana (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the quality of concrete at the pier head structure of the toll road at KM149 Padaleunyi, Bandung, using the Ultrasonic Pulse Velocity (UPV) method. UPV was chosen as a non-destructive tool for crack detection and measuring the quality and uniformity of concrete. Testing was conducted on 10 sample points, with results indicating ultrasonic wave velocities below 3000 m/s, signifying poor and unintegrated concrete condition. The average measured crack depth was 36.55 mm, potentially impacting structural stability. Based on these findings, structural repairs using high-quality crack fillers and routine monitoring are recommended to prevent further damage. Comprehensive structural evaluations are also necessary to ensure the structure can support future loads. This research provides insights into methods for evaluating and improving concrete quality in road infrastructure projects.